Understanding of cardiovascular disease among patients with hypercholesterolemia – a qualitative exploration - Samsudin, Suhaiza; Mohd Arifin, Siti Roshaidai; Md Aris, Mohd Aznan; Abdullah, Fa’iza (2019)
Cardiovascular diseases (CVD) are largely preventable but it’s still continue to be the leading cause of death worldwide. Hypercholesterolemia is one of well defined risk factors for developing CVD. • The burden of CVD is increasing rapidly in Malaysia but there are limited studies conducted on the understanding of cardiovascular disease among patient who have been identified as at risk of CVD. • Without such an understanding, an early detection and management of the cardiovascular disease within primary care setting would be challenging.